3(5k-6)-2(2k-1)=

Simple and best practice solution for 3(5k-6)-2(2k-1)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(5k-6)-2(2k-1)= equation:


Simplifying
3(5k + -6) + -2(2k + -1) = 0

Reorder the terms:
3(-6 + 5k) + -2(2k + -1) = 0
(-6 * 3 + 5k * 3) + -2(2k + -1) = 0
(-18 + 15k) + -2(2k + -1) = 0

Reorder the terms:
-18 + 15k + -2(-1 + 2k) = 0
-18 + 15k + (-1 * -2 + 2k * -2) = 0
-18 + 15k + (2 + -4k) = 0

Reorder the terms:
-18 + 2 + 15k + -4k = 0

Combine like terms: -18 + 2 = -16
-16 + 15k + -4k = 0

Combine like terms: 15k + -4k = 11k
-16 + 11k = 0

Solving
-16 + 11k = 0

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '16' to each side of the equation.
-16 + 16 + 11k = 0 + 16

Combine like terms: -16 + 16 = 0
0 + 11k = 0 + 16
11k = 0 + 16

Combine like terms: 0 + 16 = 16
11k = 16

Divide each side by '11'.
k = 1.454545455

Simplifying
k = 1.454545455

See similar equations:

| 5x+2(-2x-15)=-21 | | 4w+10=-3+10w | | 6x+4(-5x+18)=156 | | 3x+2(-3x+17)=13 | | 20x+20+4x=30x+5 | | -6x+3(4x+15)=93 | | -5x+2(6x+5)=-46 | | 1+e^2x=5e^2x | | 2x-6(-3x+5)=190 | | x^2+y^2+16x-26y+224=0 | | 6x+3(-x+17)=69 | | 5x+2(4x+6)=142 | | 9x^2+16y^2-10xy-64y-80=0 | | -4x-7(-5x-14)=-88 | | 4000=p(1+.025*5) | | 3w+4x-y+5w-18x-4y= | | 7x-4(-4x+3)=195 | | w^2+6w+19=0 | | 5+2=607 | | 8000=p(1+.125*.5) | | 6+5x=14+x | | 5(3c-5)7c=-41 | | 12x-(2x-12)=5+9x | | 4y+2y=5y+9 | | -5p-5=-11-4p | | -21+4y=42 | | p^2+12p+32=0 | | v=(3+2i)(4-i) | | -5p-5=11-4p | | 7(-3x+y)= | | 8x+3=11+7x | | 7.5/2=x |

Equations solver categories